An FBI characterization for Gevrey vectors on hypo-analytic structures and propagation of Gevrey singularities - Rodrigues, Nicholas Braun (2020)
In this work, we begin by studying the basic structure of Gevrey vectors on hypo-analytic structures, and we compare some basic properties of hypo-analytic functions and Gevrey vectors. Then we prove a FBI characterization for Gevrey vectors, and we point out the main role of the real structure bundle, in contrast to the characterization of hypo-analytic functions. We finish this work with an application, of the FBI characterization, for the propagation of singularities for solutions of the non-homogeneous system equations, associated with a real-analytic hypo-analytic structure of tube type.